ANALISIS FAKTOR-FAKTOR PERGANTIAN KANTOR AKUNTAN PUBLIK (Studi Empiris Pada Perusahaan Manufaktur di Bursa Efek Indonesia Periode 2006-2010) - Sulistiarini, Endina; Sudarno, Sudarno (Diponegoro Journal of Accounting, 2012)
This study was aim to analysed and examined Â empirically the factors that affect the manufacturing companies listed on the Indonesia Stock Exchange to change its public accounting firm. Factors tested in this study are accounting firm size (KAP), financial distress (DISTRESS), public ownership (PUBLIC), management turnover (CEO), and changes in audit committee (KA). Data collection used a purposive sampling method conducted on manufacturing companies listed on the Indonesia Stock Exchange in the period 2006-2010. The hypothesis tested in this study is using logistic regression analysis, because the independent variables are combination both metric and non metric. The results showed that the variables that influence auditor switching is the size of accounting firm (KAP) and management turnover. While the other variables examined in this study such as financial distress, public ownership, and changes in audit committee did not prove to affect the companyâ€™s decision to change the public accounting firm.